2011
DOI: 10.1074/jbc.m111.250282
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Murine Protein Kinase Cβ Gene Promotes Gallstone Formation and Alters Biliary Lipid and Hepatic Cholesterol Metabolism

Abstract: The protein kinase C (PKC) family of Ca 2؉ and/or lipid-activated serine-threonine protein kinases is implicated in the pathogenesis of obesity and insulin resistance. We recently reported that protein kinase C␤ (PKC␤), a calcium-, diacylglycerol-, and phospholipid-dependent kinase, is critical for maintaining whole body triglyceride homeostasis. We now report that PKC␤ deficiency has profound effects on murine hepatic cholesterol metabolism, including hypersensitivity to diet-induced gallstone formation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 88 publications
3
22
0
Order By: Relevance
“…Many of these new areas of investigation utilize animal models with genetically altered bile acid metabolism and/or experimental diets enriched with various bile acids. In most cases, the level of bile acid incorporated into such diets is 0.5% (wt/wt), but in some studies, the amount of supplementation far exceeds this level (4,8,10,18,29,48,50,53,55). Depending on the design of the study, such high levels of supplementation could be considered unphysiological, because the daily oral intake of bile acid is manyfold greater than the size of the animal's bile acid pool and vastly greater than the basal rate of bile acid synthesis in that animal, as measured by its daily excretion rate of acidic sterols.…”
mentioning
confidence: 99%
“…Many of these new areas of investigation utilize animal models with genetically altered bile acid metabolism and/or experimental diets enriched with various bile acids. In most cases, the level of bile acid incorporated into such diets is 0.5% (wt/wt), but in some studies, the amount of supplementation far exceeds this level (4,8,10,18,29,48,50,53,55). Depending on the design of the study, such high levels of supplementation could be considered unphysiological, because the daily oral intake of bile acid is manyfold greater than the size of the animal's bile acid pool and vastly greater than the basal rate of bile acid synthesis in that animal, as measured by its daily excretion rate of acidic sterols.…”
mentioning
confidence: 99%
“…Lastly, PKC␤ (Chr 7, 117.5 Mb, 65.7 cM) can be a positional candidate for Lith 22 gallstone susceptibility loci detected on chromosome 7, with peak linkage at 65 cM (51,61). This linkage has a mechanistic basis since we found that PKC␤ Ϫ/Ϫ mice, and not PKC␦ Ϫ/Ϫ mice, show sensitivity to diet-induced gallstone formation (39). Second, PKCs have been shown to phosphorylate and regulate the activity of several nuclear receptors (Table 1).…”
Section: Studies Implicating Pkc In the Regulation Of Diet-induced Chmentioning
confidence: 67%
“…Despite similarity of stimulatory agonists, it appears that individual PKC isoforms in this subfamily perform unique functions. For example, unlike systemic deletion of either PKC␣ (57) or PKC␥ (1), PKC␤ deletion in mice was found to have a significant impact on the body's lipid and glucose metabolism (5,(37)(38)(39)(40)(41)(42)63). Emerging evidence suggests that PKC␤ action is not only limited to triglyceride metabolism; its induction in the liver and intestinal tissues by high-fat/cholesterol diets, with or without cholic acid, enables this kinase to function as a metabolic adaptor of cholesterol homeostasis (39,42).…”
Section: Emerging Role Of Pkc␤ In Adaptiveness To High-fat/cholesteromentioning
confidence: 99%
“…Among these, PCKβ transduces insulin signalling in the liver but is also phosphorylates insulin receptor substrate (IRS)‐1 in inhibitory serine and threonine regulatory residues . Interestingly, PCKβ deficient mice have markedly increased biliary cholesterol secretion, abnormal BAs enterohepatic kinetics, and increased susceptibility to diet‐induced GSD . Therefore, PKC‐dependent pathways are a plausible molecular link between IR, cholesterol, BAs, and GSD …”
Section: Hepatic Ir As a Potential Determinant Of Gsdmentioning
confidence: 99%
“…101 Interestingly, PCKβ deficient mice have markedly increased biliary cholesterol secretion, abnormal BAs enterohepatic kinetics, and increased susceptibility to diet-induced GSD. 102 Therefore, PKC-dependent pathways are a plausible molecular link between IR, cholesterol, BAs, and GSD. 103 In addition to selective hepatic IR, systemic IR has been associated with decreased GB contractility in lean nondiabetic subjects, 104 and although the mechanisms for this observation are unknown, this abnormality might also contribute to GSD in these subjects.…”
Section: Hepatic Ir As a Potential Determinant Of Gsdmentioning
confidence: 99%